2020
DOI: 10.3390/molecules25214919
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of Polylactide by High Energy Irradiation and Photo-Curing

Abstract: Polylactide (PLA) is presently the most studied bioderived polymer because, in addition to its established position as a material for biomedical applications, it can replace mass production plastics from petroleum. However, some drawbacks of polylactide such as insufficient mechanical properties at a higher temperature and poor shape stability have to be overcome. One of the methods of mechanical and thermal properties modification is crosslinking which can be achieved by different approaches, both at the stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 103 publications
1
31
0
Order By: Relevance
“…It should be noted that a lower Young's modulus is shown in the Y60° and Y90° specimens after the UV curing process. The crossing of the line may be caused by the overirradiation of UV light in the low infill density of PLA specimens, which embrittles the material and causes the PLA filaments to fracture easily when tensile stress is applied to specimens [23]. angle, which led to the downtrend of UTS and Young's modulus value [2].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that a lower Young's modulus is shown in the Y60° and Y90° specimens after the UV curing process. The crossing of the line may be caused by the overirradiation of UV light in the low infill density of PLA specimens, which embrittles the material and causes the PLA filaments to fracture easily when tensile stress is applied to specimens [23]. angle, which led to the downtrend of UTS and Young's modulus value [2].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of the epoxy led to an increase in the chain length and reduced the mobility of the PLA chain [ 39 ]. The PLA crosslinked structure prevented the formation of inter- and intramolecular interactions of PLA crystallinity [ 40 ]; this resulted in the low crystallinity (0.6–3.6%) of the blends.…”
Section: Resultsmentioning
confidence: 99%
“…PLA behavior under irradiation is still debatable, especially at low irradiation doses. Some literature reports found that no changes in structure are detectable, despite the observed effects of the ionizing irradiation on mechanical properties of PLA, or changes have been found only if the applied dose irradiation was up to 60 kGy or higher [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%